Accurate Low-Frequency Approximation for Wires within a Two-Layered Earth - Markovski, Blagoja; Grcev, Leonid; Arnautovski-Toseva, Vesna; Kuhar, Andrijana (Obuda University, 2020)
Rigorous electromagnetic models and approximations are traditionally based on the Sommerfeld’s resolution for Hertz vector potentials. However, another resolution, based on transverse Hertz vector potentials, also exists. This paper shows that a low frequency approximation, based on this resolution, for wires embedded in a two-layered earth, is more accurate than the existing alternative. The accuracy of proposed approximation is validated for a range of different wire geometries, frequencies and earth characteristics.
Keywords: Antennas, electromagnetic analysis, frequency response, Green’s functions, grounding, integral equations, modeling, non-homogeneous media, reflection coefficient